Structural Modifications Reveal Dual Functions of the C-4 Carbonyl Group in the Fatty Acid Chain of Ipomoeassin F - Arman Khosravi; Precious Nnamdi; Alexa May; Kelsey Slattery; Robert E. Sammelson; Wei Q. Shi (Molecules)
Ipomoeassin F (Ipom-F) is a plant-derived macrocyclic resin glycoside that potently inhibits cancer cell growth through blockage of Sec61-mediated protein translocation at the endoplasmic reticulum. Recently, detailed structural information on how Ipom-F binds to Sec61α was obtained using Cryo-EM, which discovered that polar interactions between asparagine-300 (N300) in Sec61α and four oxygens in Ipom-F are crucial. One of the four oxygens is from the carbonyl group at C-4 of the fatty acid chain. In contrast, our previous structure–activity relationship (SAR) studies suggest that the carbonyl group is not essential. To resolve this discrepancy, we designed and synthesized two new open-chain analogues (10 and 11); 10 without the C-4 carbonyl had a dramatic activity loss, whereas 11 with an amide functional group was even more potent than Ipom-F. These new SAR data, in conjunction with some previous SAR information, imply two functional roles of the C-4 carbonyl: (1) to form H-bonds with N300; and (2) to regulate interactions of the fatty acid chain with membrane lipids. Impacts of these dual functions on antiproliferation depend on the overall structure of an Ipom-F derivative. Moreover, 11 can serve as a lead compound for developing future amino acid/peptide-modified analogues of Ipom-F with improved therapeutic properties.